Overview of the biochemical and genetic processes in malignant mesothelioma - Assis,Leonardo Vinícius Monteiro de (2014)
Malignant mesothelioma (MM) is a highly aggressive form of cancer, has a long latency period, and is resistant to chemotherapy. It is extremely fatal, with a mean survival of less than one year. The development of MM is strongly correlated with exposure to asbestos and with other factors, such as erionite and simian virus 40. Although various countries have banned the use of asbestos, MM has proven to be difficult to control and there appears to be a trend toward an increase in its incidence in the years to come. In Brazil, MM has not been widely studied from a genetic or biochemical standpoint. In addition, there have been few epidemiological studies of the disease, and the profile of its incidence has yet to be well established in the Brazilian population. The objective of this study was to review the literature regarding the processes of malignant transformation, as well as the respective mechanisms of tumorigenesis, in MM.